![](/images/dot.gif)
Home > Just Math
A Real Number problem (Posted on 2006-08-16) |
|
Given that x is a real number, determine all possible solutions of:
√(x-1) + √(3-x) = x² - 4x + 6
|
Submitted by K Sengupta
|
Rating: 4.0000 (2 votes)
|
|
Solution:
|
(Hide)
|
Clearly, 1<= x< =3, since x is a real number. Otherwise, one of the two expressions in the LHS would be imaginary.
Let, y = sqrt(x-1) + sqrt(3-x)
or, y2 = 2 + 2*sqrt {(x-1)(3-x)}
= 2 + 2*sqrt {1 - (x-2)^2} < = 2+2*1 = 4
or, |y| < =2-------(#)
Now, x2- 4x + 6 = (x-2)2+2 >=2--------(##)
Now, (#)and (##) is feasible only when :
x2- 4x + 6 = 2
or, x = 2.
Consequently, x =2 is the only feasible solution to the given problem. |
Comments: (
You must be logged in to post comments.)
|
![](/images/dot.gif) |
Please log in:
Forums (0)
Newest Problems
Random Problem
FAQ |
About This Site
Site Statistics
New Comments (5)
Unsolved Problems
Top Rated Problems
This month's top
Most Commented On
Chatterbox:
|